Memories in the service of the Hindu nation : the afterlife of the partition of India - Kohli, Pranav (Cambridge, New York, NY ; Cambridge University Press, 2023)
"Memories in the Service of the Hindu Nation is based on 14 months of ethnographic fieldwork in Delhi and its surroundings between 2017 and 2018 with Partition survivors from west Punjab and the North-West Frontier Province. It locates the global rise of far-right nationalism within globalisation and memories of victimhood. Focusing on Hindu nationalism in India, this book is an important and timely contribution to the literature on South Asian Partition Studies that shows how tragedy begets tragedy. It tries to answer an urgent, provocative but nevertheless necessary question: What does it mean to remember the Partition in the time of fascism? The author shows what makes up cycles of violence by connecting the reinscription of trauma in Partition memories to the self-serving justifications of the contemporary violence of Hindu nationalism. It analyses how the hegemony of Hindu nationalism has structured the narratives of Hindu Partition survivors and recruited them in the service of a putative Hindu nation"--
Prologue : the linguistic context -- Introduction : death and the problem of theodicy -- Listening to ancestors : ethnography in a milieu of memory -- Stories of Purusharth -- A story half told : the moral and political claims of Purusharth -- Sacrifice and hard work : martyrdom as theodicy -- The Purusharth of women -- The fractured nomos -- Remembering violence -- Remembering partition in the time of fascism -- Healing, victimhood and ressentiment -- Conclusion : field notes on global authoritarianism.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Political violence -- India -- History -- 20th century; Political refugees -- India -- History -- 20th century; Nationalism -- India -- History; Nationalism -- Religious aspects -- Hinduism; Purushārtha.; Theodicy; India -- History -- Partition, 1947 -- Personal narratives; Khyber Pakhtunkhwa (Pakistan) -- History; Punjab (Pakistan) -- History